Near-Infrared Reflectance Spectroscopy (NIRS) for Protein, Tryptophan, and Lysine Evaluation in Quality Protein Maize (QPM) Breeding Programs - CGIAR Research Program on Maize (2021)
In the past few years, biofortification programs designed to increase the nutritional quality of maize for human and animal consumption has received more attenti